Culex mosquitoes (Diptera: Culicidae) recorded along the Nile River in central and northern Sudan, with a key for the identification of all species of the genus known to occur in the country - Simsaa, Mishkat A. A.; Harbach, Ralph E.; Almalik, Alaa M. Ali; Ahmed, Elsheima M.; Eisa, Alwia A.; Mohamed, Asia H.; Azrag, Rasha S. (Zootaxa, 2021)
Despite the importance of Culex species as major vectors of Rift Valley fever virus, West Nile virus and the microfilariae that cause lymphatic filariasis, information on these mosquitoes in Sudan is limited to works published 65 years ago in the former Anglo-Egyptian Sudan, where some species were only recorded from areas of the territory now known as South Sudan. In this paper, we provide updated information on Culex mosquitoes collected indoors during surveillance studies conducted along the Nile River in central and northern areas of Sudan between 2012 and 2019. Of 3,411 female mosquitoes collected in Khartoum and northern states along the river, 2,560 (75%) were specimens of Culex belonging to 12 species: Cx. (Culex) antennatus (Becker, 1903), Cx. (Cux.) laticinctus Edwards, 1913, Cx. (Cux.) neavei Theobald, 1906, Cx. (Cux.) pipiens Linnaeus, 1758, Cx. (Cux.) perexiguus Theobald, 1903, Cx. (Cux.) poicilipes (Theobald, 1903), Cx. (Cux.) quinquefasciatus Say, 1823, Cx. (Cux.) simpsoni Theobald, 1905, Cx. (Cux.) sinaiticus Kirkpatrick, 1925, Cx. (Cux.) theileri Theobald, 1903, Cx. (Cux.) tritaeniorhynchus Giles, 1901 and Cx. (Culiciomyia) macfiei Edwards, 1923. This is the first record for Cx. tritaeniorhynchus and Cx. macfiei in central Sudan. The relative abundance of each species varied in different areas and seasons, but Cx. antennatus and Cx. quinquefasciatus were the most abundant indoor resting species. We provide an updated dichotomous key for the identiﬁcation of the adults of Culex mosquitoes known to occur in the Republic of the Sudan.